Single-point versus double-point injection technique of ultrasound-guided supraclavicular block: A randomized controlled study - Nitin Choudhary; Abhijit Kumar; Amit Kohli; Sonia Wadhawan; Tabish H Siddiqui; Poonam Bhadoria; Hemlata Kamat (Wolters Kluwer Medknow Publications, 2019)
Background and Aims: This study aims to compare the single-point injection and double-point injection technique of ultrasound-guided supraclavicular block with regard to the success rate, time taken to perform the procedure, onset and duration of sensory and motor block, and complications. Material and Methods: A total of 60 American Society of Anesthesiologists physical status I and II patients between 20 and 50 years of age, with body mass index ≤30 kg/m2 posted for forearm surgeries, with anticipated surgical duration more than 1 h were randomly divided into two groups: group S (single-point injection) and group D (double-point injection technique). After locating the brachial plexus with ultrasound, needle was inserted from lateral to medial direction to reach the plexus. In group D, 20 ml of inj. bupivacaine 0.5% was deposited as 10 ml each in superior (in the cluster) and inferior pocket (corner pocket) between the plexus and subclavian artery with the help of hydrodissection while in group S the total 20 ml was deposited in the superior (in the cluster) pocket. The onset of sensory and motor block was assessed using pin prick method and modified Bromage scale. Adequacy of block was ensured by assessing the ulnar, radial, and median nerve distribution. Procedural time was defined from the point of scanning the plexus till the drug was injected completely. Total sensory, motor duration, and complications if any were noted. Results: Group D had higher success rate compared to group S (96.7 vs. 83.3%; P < 0.0001). The total procedural time was significantly more in group D compared to group S (14.6 ± 2.7 vs. 10.1 ± 1.7 min; P < 0.0001). The onset of sensory and motor block was faster and the duration of sensory and motor block was significantly longer in group D. Conclusion: The adequacy of block, sensory, and motor duration was significantly high in newer double-point injection technique. However, it requires longer procedural time compared to single-point injection technique.